THE EFFECT OF REMINISCENCE THERAPY ON IMPROVING THE COGNITIVE VALUES OF THE ELDERLY AT RISK OF DEMENTIA - Hasnah, Kholifah; Kristian Nugroho, Rio (Universitas Kusuma Husada Surakarta, 2025)
Elderly is a process that a person goes through in which gradual physical and psychological decline occurs, one of which is a decline in cognitive function. Cognitive decline will cause problems in fulfilling basic needs in the elderly. One non-pharmacological intervention that can be given to elderly people with cognitive impairment is reminiscence therapy. The aim of this research is to determine the increase in the cognitive value of the elderly after being given reminiscence therapy. The method used in this research was quasi-experimental with one group pretest and posttest design. The number of subjects in this study were 25 elderly people who would be given reminiscence therapy and their cognitive scores would be measured using the Mini Mental State Examination questionnaire before and after being given the intervention. The results of the analysis showed that there was an increase in the cognitive scores of 16 samples (64%) from 0-17 (severe cognitive impairment category) to 18 - 23 (mild cognitive impairment category) and 12 samples (36%) with an increase in the average total cognitive score - average 2 (still category of severe cognitive impairment). The difference in average score is 2.9 in the pre-test and post-test scores. Conclusion: Reminiscence therapy can improve cognitive values ​​in the elderly. It is suggested that there is a need for comparative interventions to assess the effectiveness of therapy for elderly people with dementia.